Efficient CO2 capture from ambient air with amine-functionalized Mg–Al mixed metal oxides. Issue 32 (30th July 2020) - Zhu, Xuancan; Ge, Tianshu; Yang, Fan; Lyu, Meng; Chen, Chunping; O'Hare, Dermot; Wang, Ruzhu
Abstract : A new family of class 1 adsorbents is prepared using amine functionalized mixed metal oxides, which provides slit-like morphologies and defect-abundant nanostructures to achieve promising adsorption performance under ultradilute conditions. Abstract : The search for efficient amine-functionalized materials for direct air capture (DAC) of CO2 is highly important to achieve negative emissions. Here we report a new family of class 1 adsorbents for DAC by loading 67 wt% branched poly(ethylenimine) (PEI) onto Mg–Al–CO3 layered double hydroxide-derived mixed metal oxides (MMOs), which exhibit unexpectedly large CO2 uptakes (2.27 mmol g −1 ), fast kinetics (1.1 mmol g −1 h −1 ), and high stability over 20 cycles at 25 °C under 0.4 mbar CO2 . The prepared MMO nanosheets are self-assembled into spherical shaped particles with abundant slit-like mesopores and broad pore size distribution. This ideal nanostructure leads to the uniform distribution of the impregnated PEIs and optimal accessibility for CO2 molecules. The defect-abundant MMO layers provide strong electrostatic attraction to the attached polyamines, making the hybrid adsorbents thermally robust up to 300 °C. Enhanced capacity and stability are observed in the presence of moisture, thus facilitating the use of steam stripping to concentrate the desorbed CO2 .